(untitled) (Jurnal Teknologi (Sciences & Engineering), 2015)
This study concentrates on crack that occurs at PRT beam which the beam then retrofitted with carbon fibre reinforced plastic (CFRP) sheets. The beam was tested to determine crack modes and ultimate capacity before and after retrofitted. The beam was tested under static test with displacement control of 0.009mm/sec. Once the first crack appeared, the beam was unloaded and took out for retrofitting process. The beam was loaded again to failure to evaluate the effect of CFRP on the behaviour of the long span beam. Therefore, the finding of this study will guide engineers and construction practitioners to further understand the effects of CFRP sheets used in long span beam in term of load capacity and crack behaviour after retrofitting work.